2013
DOI: 10.3109/14767058.2013.845660
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure changes across gestation in patients with twin pregnancies

Abstract: In patients with twin pregnancies, the BP remains stable from 6 weeks until 30 weeks, at which time it begins to rise steadily. The 95th percentile for SBP and DBP prior to 30 weeks are ∼120 and 80 mmHg, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…In a previous study, researchers observed that BP began to rise after 30 weeks gestation during twin pregnancies. 25 Together, these studies strongly suggest that women with twin pregnancies are at increased risk for high BP as gestational age increases. Furthermore, pulse rates during the twin pregnancies were significantly higher than those during the singleton pregnancies between 11 and 30 weeks gestation.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, researchers observed that BP began to rise after 30 weeks gestation during twin pregnancies. 25 Together, these studies strongly suggest that women with twin pregnancies are at increased risk for high BP as gestational age increases. Furthermore, pulse rates during the twin pregnancies were significantly higher than those during the singleton pregnancies between 11 and 30 weeks gestation.…”
Section: Discussionmentioning
confidence: 89%
“…Поскольку многоплодная беременность является отдельным фактором риска ПЭ (относительный риск 2,9), контроль показателей АД у этой категории женщин приобретает особое значение [35], при этом их прицельный мониторинг необходим при АД>120/80 мм рт. ст., поскольку последнее соответствует 95-му процентилю кривой распределения АД в данной популяционной группе [36].…”
Section: Discussionunclassified